Evaluating authenticity in cultural tourism - Liberato, Dália (2019)
The main objective is to perceive the role of local traditions and authenticity in attracting tourists to a middle size city, Viana do Castelo (North of Portugal) as a tourism destination. The globalization and all the changes observed worldwide, at the political, economic or social level, induces tourism as an opportunity for interaction between different peoples and cultural exchange, between different values, beliefs and lifestyles. It’s pertinent to approach the creative tourism in this study, regarding its relationship with the authenticity of the destinations, since the creative experiences are characterized by the search for authentic experiences. One objective and three hypothesis have been defined: H1-Trip characteristics influence the evaluation of objective, constructive, existentialist and post-modern authenticity regarding “Sra. da Agonia” festivities; H2- A greater appreciation of authenticity corresponds to a positive assessment of the tourist experience in the 4 domains: Educational, Evasion, Aesthetic, Entertainment; H3- A better assessment of the tourist experience corresponds to a higher level of satisfaction concerning the destination. A questionnaire was applied to 299 tourists/visitors in the city of Viana do Castelo. This research concluded that: The characteristics of the trip influence the evaluation of objective, constructive, existential and post-modern authenticity, for several trip characteristics; a greater appreciation of authenticity, corresponds to a positive evaluation of the tourist experience in the 4 domains presenting the relationship between "objective authenticity and existential authenticity" and the "tourist experience" a standardized positive coefficient and statistically significant; A better tourist experience assessment corresponds to a higher level of satisfaction concerning the destination, presenting the relationship between "tourist experience" and "satisfaction" a positive and statistically significant standard coefficient.